(untitled) (Revista Contexto & Saúde, 2026)
Sepsis is a life-threatening condition characterized by infection and widespread inflammation, resulting in multiple organ dysfunction syndrome (MODS). This study aimed to evaluate whether temperature, body weight, glycemia, hematological parameters, and their ratios can be used as biomarkers in a mouse model of experimental sepsis. An experimental animal study using mice was conducted, divided into two groups: Control group (CTRL) and Sepsis group (SEP). Animals in the control group received 0.9% saline solution, whereas those in the sepsis group received an intraperitoneal injection of 20% fecal solution (1 mg/g). Clinical and laboratory biomarkers were assessed at 0, 4, 12, and 24 hours throughout the experimental protocol. It was demonstrated that, as early as 4 hours after sepsis induction, hypothermia and decreased blood glucose levels were observed in the sepsis group compared to the control group. At 24 hours, the sepsis group showed reductions in mean corpuscular volume (MCV) and platelet counts. In addition, an increase in the neutrophil-to-lymphocyte and platelet ratio (NLPR) was identified. Thus, these findings demonstrate that hypothermia, glycemia, and hematological parameters may serve as important biomarkers for the diagnosis and monitoring of sepsis.